2019
DOI: 10.3390/ijerph16162956
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Primary Treatment on Post-Traumatic Endophthalmitis in Children with Open Globe Injuries: A Study in China

Abstract: Post-traumatic endophthalmitis (PTE) is considered as one of the most serious complications after open globe injuries (OGIs), especially in children. Poor prognosis of this disease can lead to a variety of socioeconomic problems. This study aimed to investigate the clinical characteristics of pediatric OGIs and the factors associated with the development of PTE in China. 131 patients under 14 years old and needed hospitalization for management of OGIs were enrolled. There were 90 males and 41 females. 44 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
1
3
1
1
Order By: Relevance
“…Delayed repair is a risk factor for postoperative wound leakage(26), which will result in the edema of the surrounding tissue and increase the risk of wound dehiscence, thereby indirectly affecting the infection of the wound. Similar to those of studies on pediatric ocular injury (21)(22)(23)27), logistic regression analysis of this study identi ed the delayed wound repair ≥24h was the independent risk factor and compared with the that of the control group (30.4%), the incidence of endophthalmitis in patients with delayed admission≥24 h was signi cantly higher (75.0%).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Delayed repair is a risk factor for postoperative wound leakage(26), which will result in the edema of the surrounding tissue and increase the risk of wound dehiscence, thereby indirectly affecting the infection of the wound. Similar to those of studies on pediatric ocular injury (21)(22)(23)27), logistic regression analysis of this study identi ed the delayed wound repair ≥24h was the independent risk factor and compared with the that of the control group (30.4%), the incidence of endophthalmitis in patients with delayed admission≥24 h was signi cantly higher (75.0%).…”
Section: Discussionsupporting
confidence: 74%
“…This result was supported by previous studies (23,25,28) that showed foreign bodies with complex microorganisms can easily grow in suitable cultures if conditions permit. Notably, foreign bodies have not been found to increase the risk of endophthalmitis in other studies (22,27) including this present study. In addition, endophthalmitis and traumatic cataract were not statistically associated in this study, which was similar to the results of some previous studies (21,22,24) and opposite to the results of other studies (25,26).…”
Section: Discussioncontrasting
confidence: 57%
“…We suggest that prevention strategies based on age or type of injuries to be considered. For pediatric ocular injuries, prevention system or education program to avoid accidents in potentially dangerous activities should www.nature.com/scientificreports/ www.nature.com/scientificreports/ be implemented 20 . Parents or teachers have to play an important role in supervision 6 .…”
Section: Discussionmentioning
confidence: 99%
“…[4] Endophthalmitis is one of the most serious and poor prognosis complications after OGI, which is preventable by primary wound closure. [31] About one-third (33.6%) of cases underwent surgeries twice, and 12.7% of them underwent surgeries three times. Lensectomy and deep vitrectomy were the most common types of surgery performed after the initial operation.…”
Section: Discussionmentioning
confidence: 99%